Is Bulgaria Capitalist State? - Kulov, Ventseslav (Research Papers, 2018)
The main problem discussed in the article is the integral characteristics of the Bulgarian society. The author’s thesis is that contrary to the generally accepted opinion this society is not a capitalist one. To substantiate this viewpoint the author has explicated the meaning of the common name of capitalism. Based on Karl Popper’s views the author maintains that the efficient normative regulation is a requisite condition for the existence of capitalism while in present day Bulgaria this condition has not been fulfilled.